2020
DOI: 10.3389/fpls.2020.574775
|View full text |Cite
|
Sign up to set email alerts
|

TaUGT6, a Novel UDP-Glycosyltransferase Gene Enhances the Resistance to FHB and DON Accumulation in Wheat

Abstract: Fusarium head blight (FHB), a devastating wheat disease, results in loss of yield and production of mycotoxins including deoxynivalenol (DON) in infected grains. DON is harmful to human and animal health and facilitates the spread of FHB symptoms. Its conversion into DON-3-glucoside (D3G) by UDP-glycosyltransferases (UGTs) is correlated with FHB resistance, and only few gene members in wheat have been investigated. Here, Fusarium graminearum and DON-induced TaUGT6 expression in the resistant cultivar Sumai 3 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…This assumption is supported by the weak detection of canonical correlations between the fungal proteins and the wheat Cv × T_effect proteins. Despite the detection of different molecular functions already shown to be involved in plant defense, such as UDP-glucosyltransferases (Pasquet et al, 2016;He et al, 2020) and the Thi4 protein family (Yusof, 2019), the marginal detection of such patterns of abundance changes suggests that the impact of the infection and/or fungal strain genetics has only a specific and a limited effect on the host responses.…”
Section: Marginal Proteome Regulations Discriminate Wheat Cultivars Of Contrasting Fhb Susceptibilitiesmentioning
confidence: 99%
“…This assumption is supported by the weak detection of canonical correlations between the fungal proteins and the wheat Cv × T_effect proteins. Despite the detection of different molecular functions already shown to be involved in plant defense, such as UDP-glucosyltransferases (Pasquet et al, 2016;He et al, 2020) and the Thi4 protein family (Yusof, 2019), the marginal detection of such patterns of abundance changes suggests that the impact of the infection and/or fungal strain genetics has only a specific and a limited effect on the host responses.…”
Section: Marginal Proteome Regulations Discriminate Wheat Cultivars Of Contrasting Fhb Susceptibilitiesmentioning
confidence: 99%
“…Fusarium head blight (FHB) in bread wheat or barley is caused by a complex of Fusarium fungi, which may be dominated by Fusarium graminearum [ 2 ]. FHB can lead to marked yield losses [ 3 ]. Moreover, cereal grains infected with the Fusarium species may contain high levels of mycotoxins, which threaten the health of human beings and animals [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many secondary metabolites found in plants have a role in defense against herbivores, pests, and pathogens. In this study, we found that DEGs encoding terpene synthase (Vradi02g10900, Vradi02g10990, and Vradi0399s00070) involved in terpene metabolism, galactinol synthase (Vradi08g11570) involved in raffinose metabolism, β-galactosidase (Vradi06g16920), and UDP-glycosyltransferase superfamily protein (Vradi0207s00030, Vradi0387s00030, and Vradi02g04560) involved in glycosylation, cytochrome P450 superfam-ily protein (Vradi01g08930, Vradi02g06800, Vradi03g01370, and Vradi11g02370), β-glucosidase (Vradi05g21890), and alcohol dehydrogenase (Vradi06g11500) were reported to involved in plant defense mechanism against pathogens and insect pests infection [74][75][76][77][78][79][80][81][82]. Besides, we also found several DEGs belong to the family of formate dehydrogenase [83], chlorophyllase 1 [84], F-box family protein [85], methionine sulfoxide reductase [86], glutathione S-transferase family protein [87], and peroxidase superfamily [88] that are known to be involved indirectly or indirectly in plant defense mechanism against stress.…”
Section: Transcription Factors and Secondary Metabolitesmentioning
confidence: 99%